22.6k views
3 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!!

f s(x) = 2x^2 + 3x - 4, and t(x) = x + 4 then s(x) · t(x) =

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! f s(x) = 2x^2 + 3x - 4, and t(x-example-1
User Musingsole
by
5.2k points

2 Answers

5 votes

Answer:


\large\boxed{A.\ 2x^3+11x^2+8x-16}

Explanation:


s(x)=2x^2+3x-4,\ t(x)=x+4\\\\s(x)\cdot t(x)\to\text{substitute:}\\\\s(x)\cdot t(x)=(2x^2+3x-4)(x+4)\\\\\text{Use FOIL:}\ (a+b)(c+d)=ac+ad+bc+bd\\\\s(x)\cdot t(x)=(2x^2)(x)+(2x^2)(4)+(3x)(x)+(3x)(4)+(-4)(x)+(-4)(4)\\\\=2x^3+8x^2+3x^2+12x-4x-16\\\\\text{Combine like terms}\\\\s(x)\cdot t(x)=2x^3+(8x^2+3x^2)+(12x-4x)-16\\\\s(x)\cdot t(x)=2x^3+11x^2+8x-16

User Pablo Mescher
by
4.8k points
5 votes

Answer: A) 2x³ + 11x² + 8x - 16

Explanation:

s(x) · t(x) = (2x² + 3x - 4)(x + 4)

= x(2x² + 3x - 4) + 4(2x² + 3x - 4)

= 2x³ + 3x² - 4x + 8x² + 12x - 16

= 2x³ + 3x² - 4x + 8x² + 12x - 16

= 2x³ + 11x² + 8x - 16

User Tutak
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.